2021
DOI: 10.1016/j.pathol.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibodies in the Southern Region of New Zealand, 2020

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The cut-off value is 1.4 Index. Assay specificity was calculated locally as 99.6% using antenatal samples (n=300) in New Zealand [9] .…”
Section: Laboratory Analysismentioning
confidence: 99%
“…The cut-off value is 1.4 Index. Assay specificity was calculated locally as 99.6% using antenatal samples (n=300) in New Zealand [9] .…”
Section: Laboratory Analysismentioning
confidence: 99%
“…During the first wave of infection in NZ a cohort of PCR-confirmed COVID-19 cases was recruited in the Southern District Health Board (SDHB) region (3). We have previously reported on antibody dynamics in this cohort, alongside participants from other cohorts, up to 8-months post-infection (4).…”
mentioning
confidence: 99%
“…Nucleocapsid seroprevalence was used as a surrogate marker of previous SARS-CoV-2 infection. There are limitations in relying upon this marker as some individuals may not mount a nucleocapsid antibody response following SARS-CoV-2 infection, particularly if previously vaccinated, and these antibodies have been observed to wane over time [13,[20][21][22]. However, waning of anti-nucleocapsid antibodies is assay dependent, with the Roche total anti-nucleocapsid antibody assay, used in this study, reported to show high sensitivity out to at least 11.5 months post infection [23].…”
Section: Discussionmentioning
confidence: 88%